Bandwidth Enhancement of a Backfire Microstrip Patch Antenna for Pervasive Communication - Puran Gour; Ravishankar Mishra (International Journal of Antennas and Propagation)
Backfire antenna 0.265λ for bandwidth enhancement is proposed and investigated. The proposed antenna is fed by a 50 Ω coaxial feed. The bandwidth of proposed antenna for S and C band is investigated. The performance of backfire antenna is investigated by performing numerical calculation by using various mathematical formulas to determine necessary dimensions of the antenna and simulation by using commercially available Method of Moments software. Here we design proposed geometry for 3 GHz. For this geometry we achieved 52.8% bandwidth for VSWR <2, minimum return loss −20 dB, and maximum directivity 7.2 dBi.